2011
DOI: 10.1007/s12646-011-0072-3
|View full text |Cite
|
Sign up to set email alerts
|

Self as the Target and the Perceiver: A Componential Approach to Self-Enhancement

Abstract: In this paper, we review the recent literature on the debate over the value of self-enhancement. Past studies fall into two distinct sets, each in the context of a different research tradition. The componential approach to selfenhancement integrates these two divergent perspectives and takes seriously the interplay of self-perception and interpersonal perception. Instead of global indices, the componential approach identifies specific components of person perception. By partitioning the components in selfperce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nearly all studies examining individual differences in self-knowledge face tricky definitional issues with the operationalization of self-knowledge. Both of the two most commonly used methods for calculating individual differences in self-enhancement have important confounds (as noted by [32] [4] [24]). The social comparison approach (asking participants to rate themselves relative to others) confounds self-enhancement with actually possessing positive traits, because people who rate themselves more positively than they rate others may not be self-enhancers if they in fact have exceptional personalities.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all studies examining individual differences in self-knowledge face tricky definitional issues with the operationalization of self-knowledge. Both of the two most commonly used methods for calculating individual differences in self-enhancement have important confounds (as noted by [32] [4] [24]). The social comparison approach (asking participants to rate themselves relative to others) confounds self-enhancement with actually possessing positive traits, because people who rate themselves more positively than they rate others may not be self-enhancers if they in fact have exceptional personalities.…”
Section: Introductionmentioning
confidence: 99%
“…While religious people are often inclined to help others (altruistic values), religion also plays a crucial role in molding one’s self-concept. This heightened focus on the self can result in self-enhancement tendencies (Kwan et al, 2011). The self-concept is central to Christianity, and previous findings show that Christians actually seek to self-enhance more than the non-religious (Sedikides & Gebauer, 2021), particularly when maintaining a favorable self-view of a “good Christian” is important (Zell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, various forms of deviant and counterproductive behaviors can be relevant outcomes of employee OP. In particular, to the extent that obsessively passionate employees are more aggressive and competitive (Carbonneau et al, 2008), they are also more likely to strategically use their passion to self-enhance and prove themselves (Lafrenière et al, 2013), which has been previously shown to result in uncivil behaviors (Kwan et al, 2011; Leary, 2007). Thus, workplace incivility may be a strategic behavioral outcome of employee OP that warrants future investigation.…”
Section: Discussionmentioning
confidence: 99%